The Greatest Possible Freedom - Burri, Thomas (Nomos Verlagsgesellschaft mbH & Co. KG, 2015)
The book entitled 'The Greatest Possible Freedom' tells the story of natural persons in the internal market. The first part contains a thick chronological description of the case-law of the Court of Justice of the European Union on free movement of persons and services, including the hitherto largely neglected coordination of social security. In this sizeable body of case-law including roughly 1400 decisions the book then traces the evolution and spin of certain interpretive formulas. Broad formulas like the greatest possible freedom or coordinative formulas like simple coordination are thus examined and their almost eerie power comes to light.